Effect of vitamin D source and amount on vitamin D status and response to endotoxin challenge - L.P. Blakely; T.L. Wells; M.F. Kweh; S. Buoniconti; M. Reese; P. Celi; C. Cortinhas; C.D. Nelson (Journal of Dairy Science, 2023)
ABSTRACT: The objectives were to test the effects of dietary vitamin D3 [cholecalciferol (CHOL)] compared with 25-hydroxyvitamin D3 [calcidiol (CAL)] on vitamin D status and response to an endotoxin challenge. Forty-five Holstein bull calves (5 ± 2 d of age) were blocked into weekly cohorts, fed a basal diet that provided 0.25 µg/kg body weight (BW) CHOL, and assigned randomly to 1 of 5 treatments: control [(CON) no additional vitamin D], 1.5 µg/kg BW CHOL (CHOL1.5), 3 µg/kg BW CHOL (CHOL3), 1.5 µg/kg BW CAL (CAL1.5), or 3 µg/kg BW CAL (CAL3). Calves were fed milk replacer until weaning at 56 d of age and had ad libitum access to water and starter grain throughout the experiment. Treatments were added daily to the diet of milk replacer until weaning and starter grain after weaning. Measures of growth, dry matter intake, and serum concentrations of vitamin D, Ca, Mg, and P were collected from 0 to 91 d of the experiment. At 91 d of the experiment, calves received an intravenous injection of 0.1 µg/kg BW lipopolysaccharide (LPS). Clinical and physiological responses were measured from 0 to 72 h relative to LPS injection. Data were analyzed with mixed models that included fixed effects of treatment and time, and random effect of block. Orthogonal contrasts evaluated the effects of (1) source (CAL vs. CHOL), (2) dose (1.5 vs. 3.0 µg/kg BW), (3) interaction between source and dose, and (4) supplementation (CON vs. all other treatments) of vitamin D. From 21 to 91 d of the experiment, mean BW of supplemented calves was less compared with CON calves, but the effect was predominantly a result of the CHOL calves, which tended to weigh less than the CAL calves. Supplementing vitamin D increased concentrations of 25-hydroxyvitamin D in serum compared with CON, but the increment from increasing the dose from 1.5 to 3.0 µg/kg BW was greater for CAL compared with CHOL (CON = 18.9, CHOL = 24.7 and 29.6, CAL = 35.6 and 65.7 ± 3.2 ng/mL, respectively). Feeding CAL also increased serum Ca and P compared with CHOL. An interaction between source and dose of treatment was observed for rectal temperature and derivatives of reactive metabolites after LPS challenge because calves receiving CHOL3 and CAL1.5 had lower rectal temperatures and plasma derivatives of reactive metabolites compared with calves receiving CHOL1.5 and CAL3. Supplementing vitamin D increased plasma P concentrations post-LPS challenge compared with CON, but plasma concentrations of Ca, Mg, fatty acids, glucose, β-hydroxybutyrate, haptoglobin, tumor necrosis factor-α, and antioxidant potential did not differ among treatments post-LPS challenge. Last, supplementing vitamin D increased granulocytes as a percentage of blood leukocytes post-LPS challenge compared with CON. Supplementing CAL as a source of vitamin D to dairy calves was more effective at increasing serum 25-hydroxyvitamin D, Ca, and P concentrations compared with feeding CHOL. Supplemental source and dose of vitamin D also influenced responses to the LPS challenge.